Corporate Social Responsibility: Keterkaitan Letak Geografis Terhadap Desain Program dan Pelaporan Perusahaan - Deasy Sagitaningrum; Dianne Frisko (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2015)
This research aims to analyze the role of the geographical area surrounds company in the linkage with the design of corporate social responsibility (CSR) program and CSR reporting. This study uses qualitative approach by comparing two companies in different location. They are Indonesian companies (PT Indo Tambangraya Megah Tbk) and Australian company (OZ Minerals). Content analysis method is used to collect the public data. The result conveys factual information that the geographical area, natural environment, local value, and government policy create the differences for each company in designing the CSR program and the ways companies provide CSR report. Company which is located in cultural society are tend to design the CSR program by regarding the cultural values. Company which is located in certain jurisdiction tends to report CSR based on the regulated standard. Moreover, environment, education, health, and economic condition are also considered in designing CSR programs.